The Involvement of Local Community in The Tourist Attractions of Baliwoso Upadesa, Pengotan, Bangli - Nyan, Fei; Anom, I Putu; Narottama, Nararya (Institut Pariwisata dan Bisnis Internasional, 2023)
Bali, which is essentially the center of Indonesian tourism which is known by all foreign tourists, has all kinds of tourism that tourists need. One of the tourism sectors is special interest tourism, especially in rural areas. The involvement of local community participation plays an important role in the development and preservation of the environment and local resources. However, most of them work as farmers, of course they lack knowledge and experience in the field of tourism. So that in involving the community it is necessary to do training first. This study aims to analyze the form of local community involvement in Pengotan Village by using the theory of participation and the function of human resources. This research was conducted by collecting qualitative data. Data obtained from interviews and observations. After the data was obtained, the researchers analyzed the data using Miles and Huberman. The results of this study found that the Pengotan Village Community involved in Baliwoso participated actively in a top-down or bottom-up manner, starting from managerial functions to the operational functions of Upadesa Baliwoso. This provides a boost to employment opportunities or additional income by working to meet the operational needs of tourists visiting Baliwoso.